Concurrent Occurrence of Avian Encephalomyelitis and Vitamin A Deficiency In a Commercial Broiler Chicken Flock - ABBASABADI, ΒΜ; SEIFI, S; GOLSHAHI, H (Journal of the Hellenic Veterinary Medical Society, 2021)
Avian encephalomyelitis (AE) is accounted for a common infectious disease in poultry, which particularly targets the central nervous system and various parenchymatous organs of chickens.Vitamin A supplementation is considered as a viable option to strengthen the immune system in neonates. Vitamin A deficiency in broilers decreases the ability to synthesize specific antibodies and weakens the lymphocyte proliferation response leading to epithelial metaplasia. In the present study, the effect of vitamin A deficiency on the occurrence of AE in a day old commercial broiler chicken flock was evaluated.Twenty, Two-Day-old paralyzed chickens, had been referred to the clinic of Veterinary School.The chicks were selected from a broiler flock with 13,000 birds purchased from a broiler breeder flock, all vaccinated against the AE virus. After examination, ataxia, trembling, lateral recumbency, and incoordination were observed in the chickens. The chickens were euthanized, and the tissue samples from their brain, heart, and proventriculus were then collected for microscopic evaluation. According to microscopic studies, non-supportive encephalomyelitis was noted in the cerebellum and cerebrum. In the myocardium, fiber degeneration and lymphocytic aggregates between the muscle fibers were evidenced.The proventriculus in chickens revealed hyperplastic and thickened mucosa, and there was squamous metaplasia for some of the mucosal glands. Furthermore, some multifocal aggregations of lymphocytes were observed in the tunica muscularis layer of the proventriculus.Our findings showed that vitamin A deficiency in a broiler breeder farm might be had a significant effect on the occurrence of AE in their hatched chicks. This study, to the best of the authors’ knowledge, is the first report of concurrent occurrence of avian encephalomyelitis and vitamin A deficiency in a Two-Day-old commercial broiler chicken flock in north of Iran.